2018
DOI: 10.1186/s10195-018-0508-9
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural adaptation and validation of the Italian versions of the Kujala, Larsen, Lysholm and Fulkerson scores in patients with patellofemoral disorders

Abstract: BackgroundThe Kujala, Fulkerson, Larsen and Lysholm questionnaires have been demonstrated to be reliable and sensitive in assessing patients with patellofemoral pathology. The purpose of this study is to translate and cross-culturally adapt into Italian the English versions of the Kujala, Fulkerson, Larsen and Lysholm questionnaires, and undertake reliability and validity evaluations of the Italian versions of these scores in patients with patellofemoral pathology.Materials and methodsThe cross-cultural adapta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 16 publications
1
42
0
Order By: Relevance
“…Original and revised scores were intended for in-person clinician administration, although subsequent studies have documented using the score as a patient-completed questionnaire [2,10]. There are consistent reports of no floor or ceiling effects (i.e., <15% of patients scoring the lowest or highest score, respectively) [3,5,8,9]. Ra et al have reported no significant differences between the IKDC subjective and the LKSS in terms of the amount of ceiling effect and the correlation with one leg hope scale in patients with ACL reconstruction [23].…”
Section: Outcome Toolsmentioning
confidence: 99%
See 3 more Smart Citations
“…Original and revised scores were intended for in-person clinician administration, although subsequent studies have documented using the score as a patient-completed questionnaire [2,10]. There are consistent reports of no floor or ceiling effects (i.e., <15% of patients scoring the lowest or highest score, respectively) [3,5,8,9]. Ra et al have reported no significant differences between the IKDC subjective and the LKSS in terms of the amount of ceiling effect and the correlation with one leg hope scale in patients with ACL reconstruction [23].…”
Section: Outcome Toolsmentioning
confidence: 99%
“…Activity levels of 6-10 can only be achieved if the person participates in recreational or competitive sport. Studies have consistently reported no floor or ceiling effects in those with a knee injury or osteoarthritis (OA) [3,5,8,12].…”
Section: Outcome Toolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each patient was followed up by telephone or outpatient visit every month after surgery and every 3 months after 3 months after surgery. Lyshohn score (excellent: greater than 90 points, good: 80-90 points, better: 70-79 points, poor: less than 70 points), medial shift of patella, Kujala score, VAS, and surgical complications were used and evaluated for efficacy evaluation [6,[12][13][14][15].…”
Section: Postoperative Managementmentioning
confidence: 99%